Efforts to Improve Students' Mathematical Problem-Solving Ability by Applying Guided Discovery Method in Class VII SMP PAB 2 Helvetia T.A. 2021/2022 - Andra, Delvi (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to determine: (1) How the teacher's efforts to improve students' mathematical problem-solving skills by applying the guided discovery method, (2) How to increase the mathematical problem-solving abilities of students in class VII SMP PAB 2 Helvetia T.A. 2021/2022 after the guided discovery method is applied. This type of research is classroom action research. The subjects in this study were seventh grade students of SMP PAB 2 Helvetia T.A. 2021/2022, 1 class from 6 existing classes, namely class VII-6, totaling 15 students. The object of this research is the student's problem-solving ability on the set material by applying the guided discovery method. The research instruments used were tests, observations and documentation. The study consisted of 2 cycles, each consisting of 2 meetings. The increase in problem solving ability can be seen from the level of students' ability to solve problems, namely in the initial problem solving ability test with an average value of 35 (very low), in the first cycle problem solving ability test with an average value of 55.5 (very low), and on the problem-solving ability test in Cycle II with an average score of 80.6 (high). In addition, the ability of researchers to manage lessons has increased from Cycle I to Cycle II, namely from the total initial activities, core activities, and closing in Cycle I of 61.8 and in Cycle II of 86.5 and N-Gain obtained is 0, 5. It can be concluded, that the application of the guided discovery method can improve the mathematical problem solving ability of class VII students of SMP PAB 2 Helvetia because the problem solving ability of students has reached the minimum target of problem solving ability, which is 85% of students who take the test reach a mastery level of at least 70 (TKPM). currently).